2016
DOI: 10.1097/wnr.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Reading changes in children and adolescents with dyslexia after transcranial direct current stimulation

Abstract: Noninvasive brain stimulation offers the possibility to induce changes in cortical excitability and it is an interesting option as a remediation tool for the treatment of developmental disorders. This study aimed to investigate the effect of transcranial direct current stimulation (tDCS) on reading and reading-related skills of children and adolescents with dyslexia. Nineteen children and adolescents with dyslexia performed different reading and reading-related tasks (word, nonword, and text reading; lexical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 18 publications
7
90
2
1
Order By: Relevance
“…In a related study involving children and adolescents with dyslexia and similar age range, this electrode montage was compared with cathodal tDCS over the left parieto-temporal region (the anode placed over the right homologue region) in a single session. Left parieto-temporal anodal tDCS induced a reduction in the number of errors during text reading, and left parieto-temporal cathodal tDCS resulted in increases of errors (Costanzo et al, 2016b). Therefore, tDCS could be an effective tool to modulate reading mechanisms in children with dyslexia, although future studies will have to determine the suitability of tDCS as a therapeutic approach in larger detail.…”
Section: Dyslexiamentioning
confidence: 99%
“…In a related study involving children and adolescents with dyslexia and similar age range, this electrode montage was compared with cathodal tDCS over the left parieto-temporal region (the anode placed over the right homologue region) in a single session. Left parieto-temporal anodal tDCS induced a reduction in the number of errors during text reading, and left parieto-temporal cathodal tDCS resulted in increases of errors (Costanzo et al, 2016b). Therefore, tDCS could be an effective tool to modulate reading mechanisms in children with dyslexia, although future studies will have to determine the suitability of tDCS as a therapeutic approach in larger detail.…”
Section: Dyslexiamentioning
confidence: 99%
“…Costanzo and colleagues were the first to study the effect of tDCS on young populations with DD. Firstly, the authors explored the optimal polarity of the stimulation for children and adolescents with DD in a single session intervention (Costanzo et al, 2016a). The authors found significant text reading accuracy improvement after left anodal/right cathodal tDCS and an increase in errors after left cathodal/right anodal tDCS.…”
Section: Introductionmentioning
confidence: 99%
“…Dominguez et al (2014), for example, enhanced performance in one participant with aphasia during phonological tasks by simultaneously applying cathodal stimulation to the RIFG, to reduce its hyperactivity, and anodal stimulation to the LIFG, to enhance its activity. Similarly, Costanzo et al (2016a, b) showed that simultaneous tDCS with anodal stimulation over a left temporoparietal target and cathodal stimulation over its right homologous region, improved reading performance in participants with dyslexia, while reversing the stimulation polarity for the same targets hindered performance (Costanzo et al 2016b). Similarly, Smirni et al (2017) investigated phonemic fluency in healthy participants with rTMS and found decreased performance when inhibitory stimulation was applied to the LIFG, but increased performance when applied to the RIFG.…”
Section: Discussionmentioning
confidence: 98%